Fecal Immunochemical Tests Compared with Guaiac Fecal Occult Blood Tests for Population-Based Colorectal Cancer Screening. (2012) - Rabeneck, Linda; Rumble, R Bryan; Thompson, Frank; Mills, Michael; Oleschuk, Curtis; Whibley, Alexandra; Messersmith, Hans; Lewis, Nancy; The FIT Guidelines Expert Panel,
Abstract : Colorectal cancer (CRC) is the second most common cause of cancer deaths in Canadian men and women – accounting for almost 12% of all cancer deaths. In Ontario, it is estimated that 8100 persons were diagnosed with CRC in 2011, and 3250 died from the disease. CRC incidence and mortality rates in Ontario are among the highest in the world. Screening offers the best opportunity to reduce this burden of disease. The present report describes the findings and recommendations of Cancer Care Ontario's Fecal Immunochemical Tests (FIT) Guidelines Expert Panel, which was convened in September 2010 by the Program in Evidence-Based Care. The purpose of the present guideline is to evaluate the existing evidence concerning FIT to inform the decision on how to replace the current guaiac fecal occult blood test with FIT in the Ontario ColonCancerCheck Program. Eleven articles were included in the present guideline, comprising two systematic reviews, five articles reporting on three randomized controlled trials and reports of four other studies. Additionally, one laboratory study was obtained that reported on several parameters of FIT tests that helped to inform the present recommendation. The performance of FIT is superior to the standard guaiac fecal occult blood test in terms of screening participation rates and the detection of CRC and advanced adenoma. Given greater specimen instability with the use of FIT, a pilot study should be undertaken to determine how to implement the FIT in Ontario.